Why Do People Hate Other Groups? The Role of Perceived Threat as Mediator The Effect of Group Identification Toward Group Based Hatred - Nurhamida, Yuni; Muluk, Hamdi; Milla, Mirra Noor (Makara Human Behavior Studies in Asia, 2023)
This study aimed to investigate the formation of group-based hatred in the context of latent conflict, as previous studies have predominantly explored the consequences of hatred in intractable conflicts. Group identification was hypothesized to lead to hatred of another group through perceived threat as a mediator, with the types of threat formulated from historical conflict narratives. The research context was the latent Muslim-PKI conflict in Indonesia. Realistic feelings of threat are formulated based on the narrative that the PKI (Indonesian Communist Party) is perceived to be resurging and trying to change the foundation of the state into communism. Symbolic threat comes from the narrative that PKI resurgence aims to spread communist ideology. This study surveyed 508 Muslim Indonesian citizens aged at least 18 years. The results indicated that perceived realistic and symbolic threats fully mediated the influence of group identification as Muslims on hatred towards PKI. Consistent with the hypothesis, the results demonstrated that hatred can also occur in the context of latent conflict, with perceived threat mediating the relationship between group identification and group-based hatred, and the types of threat were rooted in the historical conflict.